Human Resource Competency Development as a Strategy in Improving The Performance of Micro, Small and Medium Enterprises in Kupang City, East Nusa Tenggara - Manteiro, Maria C. B.; Rohi Bire, Amram; Ringa, Maria Bernadetha; Hipir, Sascia D (Jurnal Ekonomi, 2024)
The problem in the study is that the competence of human resources in the MSME industry sector is still lacking, this can be seen from the lack of knowledge, skills and abilities of employees, such as lack of knowledge of management skills, lack of work skills such as mastery of automation system technology and e-commerce in the field of marketing, there are still limited employee abilities in terms of creativity and innovation, lack of communication and skilled service. This has an impact on the performance of MSMEs. In facing the above problems, an appropriate competency development strategy is needed while the strategies carried out are training programs, leadership development, access to technology, networking, access to capital, monitoring and evaluation. The objectives of this study are 1) To know the competence of human resources in small and small businesses in the city of Kupang .2) To find out how the right strategy is to develop human resource competencies in improving the performance of small and small businesses. This research uses a qualitative descriptive method and formulates the right strategy in developing human resource competencies. The determination of samples in this study was carried out in 4 sub-district clusters, namely Oebobo District, Kota Raja, Kelapa Lima and Oesapa with a purposive non-probability sampling sampling technique, namely selecting human resources for MSMEs in accordance with the set criteria. Data collection uses interview, observation, questionnaire and documentation techniques. The result of this study is the concept of human resource development strategies for MSMEs in improving MSME performance.